2013
DOI: 10.1371/journal.pone.0055264
|View full text |Cite|
|
Sign up to set email alerts
|

The Two-Component Adjuvant IC31® Boosts Type I Interferon Production of Human Monocyte-Derived Dendritic Cells via Ligation of Endosomal TLRs

Abstract: The aim of this study was to characterize and identify the mode of action of IC31®, a two-component vaccine adjuvant. We found that IC31® was accumulated in human peripheral blood monocytes, MHC class II positive cells and monocyte-derived DCs (moDCs) but not in plasmacytoid DCs (pDCs). In the presence of IC31® the differentiation of inflammatory CD1a+ moDCs and the secretion of chemokines, TNF-α and IL-6 cytokines was inhibited but the production of IFNβ was increased. Sustained addition of IC31® to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…This is in accord with the observation that IC31 was the only adjuvant among the three without highly upregulated DEGs belonging to GO terms for innate inflammatory responses. The observed limited pro-inflammatory transcript expression is in line with a previous report that IC31 mainly targets monocyte-derived DCs by increasing the level of IFN-β and limiting the production of the pro-inflammatory cytokines TNF-α and IL-631.…”
Section: Discussionsupporting
confidence: 91%
“…This is in accord with the observation that IC31 was the only adjuvant among the three without highly upregulated DEGs belonging to GO terms for innate inflammatory responses. The observed limited pro-inflammatory transcript expression is in line with a previous report that IC31 mainly targets monocyte-derived DCs by increasing the level of IFN-β and limiting the production of the pro-inflammatory cytokines TNF-α and IL-631.…”
Section: Discussionsupporting
confidence: 91%
“…It stimulates the immune system via the TLR9/MyD88-dependent pathway. IC31 ® induces potent Th1 immune response in mice (Schellack et al, 2006) and it has been shown in vitro that IC31 ® modulates the cytokine profile of human dendritic cells which is important for protection against intracellular pathogens (Lingnau et al, 2007;Szabo et al, 2013). To our knowledge, this adjuvant has not been used in horses before.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, using cells from pre-tumor cirrhotic patients, we were able to expand potentially tumor-reactive multifunctional T-cells in a significant minority of subjects using 15mer peptide antigens. Further optimization of the approach with techniques such as codon-optimized DNA [44], co-transfection with cytokine -encoding DNA [45–47], or co-transfection with PAMPs [4850] could increase the frequency of tumor-reactive T-cells generatable with cell-based vaccinations. We postulate that translation of an optimized MoDC approach using HCC-related antigens in pre-tumor cirrhotic patients has the potential to prevent or delay progression to hepatocellular carcinoma in this high risk population.…”
Section: Discussionmentioning
confidence: 99%